THE EFFECTIVENESS OF PLATELET RICH FIBRIN, CONNECTIVE TISSUE GRAFT AND THEIR COMBINATION IN THE CLOSURE OF GINGIVAL RECESSION: A SYSTEMATIC REVIEW - Dian Anggraini; Irma Ervina; Aini Hariyani Nasution (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Connective Tissue Graft (CTG) is one of the techniques in gingival recession treatment, but considering the morbidity of using CTG, biomaterials such as Platelet Rich Fibrin (PRF) can be an alternative in gingival recession closure treatment. This systematic review aims to compare and evaluate the use of PRF, CTG and their combination in gingival recession closure. Review: An electronic literature search in Medline (PubMed), Google Scholar, and Elsevier (Sciencedirect) was conducted to identify Randomized Clinical Trial (RCT) reporting on the treatment of gingival recession using PRF, CTG or a combination of both from 2018 to 2023 in English. This systematic review was conducted following the Preferred Reporting Items for Systematic review (PRISMA) guidelines. The parameters assessed in the RCTs were: recession depth (RD), clinical attachment level (CAL), keratinized gingival width and height (KTW, KTH), probing depth (PD), gingival thickness (GT) and patient discomfort after surgery assessed by VAS (Visual Analog Scale). Based on the 1,152 articles retrieved, there were only five RCTs eligible for systematic review. Four articles compared the use of PRF with CTG, and one article compared the use of CTG with the combination of CTG + PRF in gingival recession closure. Conclusion: The use of PRF, CTG, and a combination of both were effective in closing gingival recession. The use of CTG gave better results in increasing gingival thickness and keratinized gingival width compared to the use of PRF, but the combination of CTG and PRF gave significant results in keratinized gingival height and decreasing recession depth compared to the use of CTG alone. Thus, the combination of CTG and PRF may be a more promising gingival recession closure treatment option.